EFEKTIVITAS PENGENDALIAN PRODUK RUSAK DAN CACAT DALAM MENEKAN BIAYA PRODUKSI DI INDUSTRI MANUFAKTUR PESAWAT - Satria, Muhammad Rizal; Nadiahtudin, Azizah Fauziah (Universitas Logistik dan Bisnis Internasional, 2025)
Product that have good quality will create satisfaction for customers with the product provided by the corporation. Spoilage or defects in products will influence how production cost is calculated. Because when executing production activities, corporations often experience spoilage and defects in their products, which in turn can increase costs and harm the company. This research aims to determine the effect of spoilage cost and defective cost on aircraft component production costs at PT Dirgantara Indonesia. This research was performed with a probabilty sampling techniques. Sample data is obtained from financial reports for the period 2020-2023 and processed using SPSS Statistic 27 with Normality Test, Product Moment Correlation, Multiple Linear Regression Analysis, Coefficient of Determination, t Test and F Test. The results of the reseacrch partially show that spoilage cost will influence the production cost of aircraft components, but defective cost has no influence on the production cost of aircraft components. The results of the research simultaneously show the influence of spoilage cost and defective cost on the production costs of aircraft components at PT Dirgantara Indonesia.